Seen and unseen visual cultures of imperialism - Fotouhi, Sanaz; Zeiny, Esmaeil (Studies on performing arts & literature of the Islamicate world, 2018)
"Seen and Unseen teases out and explores how visual mediums construct visual cultures that often create limited perspectives of certain issues and groups, specific to this volume, the representation of Islam and Muslims. It deals with fixed and stereotypical visual representations and explores alternative and challenging visual representations which reconstruct and dismantle existing belief systems. It approaches the topic from a vantage point of diverse multiple perspectives. Covering issues from Brunei, Iran, Egypt, and England and cyberspace, essays examine the visual cultures of how Islam and Muslim people are understood, misunderstood, misrepresented, or even embraced visually. Scholars in this volume draw on historical paintings, books and their covers, photography, and news to demonstrate the diversity and sometimes contradictory visual cultures that construct and adhere meaning to how Islam and Muslim people are seen.